STRATEGI PENINGKATAN DAYA SAING INDUSTRI KECIL MIKRO KERAJINAN ANYAMAN BAMBU - Susilowati, Lina; Munawaroh, Munawaroh; Setyani, Nanik Sri (STKIP PGRI Jombang, 2023)
This research aims at woven bamboo handicrafts which are one of the superior products of Magetan Regency. The problem that occurs is that innovation is not optimal, because the quality of the workforce is still low. Bamboo woven handicraft products cannot yet have an export market. The lack of coordination between craftsmen, distributors and the government resulted in a weak institutional structure. The purpose of this research is to determine the strategy for increasing the competitiveness of the small bamboo woven handicraft industry in the Ringinagung area, Magetan district. The method used is analytical descriptive. The instrument in the form of a questionnaire given to 5 key respondents. The research used the Process Hierarchy Analysis (AHP) technique. The results of the study show that there are five areas of strategy including 1). Innovation 2). HR, 3). Production , 4). Marketing, and 5) Institutional